VISUAL OUTCOMES FOLLOWING CATARACT SURGERY WITH INTRAOCULAR LENS IMPLANTATION - Dr. Manika jain (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Cataract surgery with intraocular lens implantation represents one of the most successful medical interventions globally. Understanding local visual outcomes is essential for quality assurance, patient counseling, and healthcare planning. This study aimed to evaluate visual outcomes following cataract surgery and identify factors associated with postoperative visual acuity achievement.Methods: A prospective observational cohort study was conducted at Lord Buddha Koshi Medical College & Hospital from June to December 2022. A total of 170 patients aged 40 years and above undergoing phacoemulsification with IOL implantation were recruited using consecutive sampling. Comprehensive preoperative evaluation included visual acuity assessment, cataract grading, biometry, and comorbidity screening. Primary outcome was achievement of good functional vision (≥20/40) at three months postoperatively. Statistical analysis employed chi-square tests, independent t-tests, and multivariate logistic regression using SPSS version 25.0.Results: Overall success rate was 83.5% for achieving good functional vision (≥20/40). Excellent visual outcomes included 37.6% achieving 20/20 or better and 45.9% achieving 20/25-20/40 vision. Patient satisfaction was high with 90.6% reporting satisfaction or very high satisfaction. Significant predictors of poor outcomes included advanced age (OR=1.04 per year, p=0.032), dense cataracts (OR=4.26, p=0.001), diabetic retinopathy (OR=3.96, p=0.006), and age-related macular degeneration (OR=5.12, p=0.016). Complication rates remained low with intraoperative complications in 8.2% and postoperative complications in 7.1% of cases. Spectacle independence for distance vision was achieved in 51.8% of patients.Conclusion: Cataract surgery with IOL implantation demonstrated excellent visual outcomes and high patient satisfaction, meeting international benchmarks. Age, cataract density, and pre-existing ocular comorbidities significantly influenced surgical success, emphasizing the importance of comprehensive preoperative evaluation and appropriate patient selection.